Socialism and American Life, Volume I - Egbert, Donald Drew; Bassett, Thomas D. (Princeton, NJ : Princeton University Press, 2015)
"Easily the most comprehensive and useful work on American socialism, including its history, theories, and impact on life, culture, and economic and political parties in the United States, is as important a contribution as the essays. Hereafter, students of practically all phases of American life will turn to it for help and guidance."-U.S. Quarterly Book Review.Originally published in 1952.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.
Frontmatter -- Preface to Volume 1 -- Contents. Volume 1 -- INTRODUCTION. Terminology and Types of Socialism / Egbert, Donald Drew / Persons, Stow -- CHAPTER 1. Socialism in European History to 1848 / Harbison, E . Harris -- CHAPTER 2. European Socialism Since 1848 / Laidler, Harry W. -- CHAPTER 3. The Religious Basis of Western Socialism / Mollegen, Albert T . -- CHAPTER 4. Christian Communitarianism in America / Persons, Stow -- CHAPTER 5. The Secular Utopian Socialists / Bassett, D . Seymour -- CHAPTER 6. The Background and Development of Marxian Socialism in the United States / Bell, Daniel -- CHAPTER 7. American Socialism and the Socialist Philosophy of History / Bowers, David F. -- CHAPTER 8. The Philosophical Basis of Marxian Socialism in the United States / Hook, Sidney -- CHAPTER 9. The Influence of Marxian Economics on American Thought and Practice / Sweezy, Paul M. -- CHAPTER 10. American Marxist Political Theory / Herberg, Will -- CHAPTER 11. Sociological Aspects of American Socialist Theory and Practice / Moore, Wilbert E. -- CHAPTER 12. The Psychology of American Socialism / Hartmann, George W. -- CHAPTER 13. American Writers on the Left / Thorp, Willard -- CHAPTER 14. Socialism and American Art / Egbert, Donald Drew -- Acknowledgments -- Index to Volume 1
Mode of access: Internet via World Wide Web.
In English.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 08. Jul 2019)
Keywords: Socialism -- Bibliography; Socialism -- History; Socialism -- United States; 2 -- isacsh